KEMAMPUAN MENULIS CERPEN SISWA KELAS IX SMP NEGERI 1 AMANDRAYA - Halawa, Hironimus (Universitas Nias Raya, 2025)
The aim of this research is to determine and describe the short story writing abilities of class IX students of SMP Negeri 1 Amandraya for the 2023/2024 academic year. This type of research is descriptive using a quantitative approach. The research instrument was the population's ability to write short stories and the research sample was 31 class IX students. The results of the research show that the short story writing ability of class IX students of SMP Negeri 1 Amandraya has an average score of 62.90 and is included in category D (Poor). Based on the results of this research, it can be concluded that the ability to write short stories of class IX students of SMP Negeri 1 Amandraya varies greatly, there are those who are able to write short stories well and there are still those who are not able to write short stories well based on the assessment criteria for short story writing. Suggestions 1) Students should practice writing more both at school and outside of school, so that students' writing skills become better. 2) Teachers should improve learning regarding short story writing skills based on the building blocks of short stories. 3) For researchers as input in increasing knowledge and insight regarding the ability to write short stories and as a provision for the future when becoming a teacher. 4) For future researchers as input and comparison material in conducting research related to writing ability, especially the ability to write short stories.